KONSENTRASI LILIN DAN KEMASAN POLIETILEN TERHADAP UMUR SIMPAN BUAH SAWO (Achras zapota L.) - Ririn Rahayu; Fitria Riany Eris (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2017)
Waxing and wrapping are one way that can be used to extend the shelf life of horticultural products. By doing waxing and wrapping on Sapodilla, it was expected to increase the shelf life of the fruit, so in marketing, Sapodilla quality could be improved. This research was used to know the effect of wax concentration and polyethylene wrapping on shelf life in Sapodilla. This study using Randomized Completely Block Design. The treatment in this research was beeswax (Control, 3%, 6%, 9% and 12% that applied in 30 minutes soaking and Polyethylene Wrapping (polyethylene wrapping and without polyethylene wrapping). The result showed that sapodilla coated with a wax concentration of 9% and polyethylene wrapping had longer shelf life for 12 days.Keywords: Polyethylene, Sapodilla, Waxing, Wrapping